Livelihood and Revenue: Role of rattans among Mongoloid tribes and settlers of Andaman and Nicobar Islands, India - Senthilkumar, U.; Ritesh, K. C.; Sanjappa, M.; Narasimhan, D.; Uma Shaanker, R.; Ravikanth, G. (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">The Andaman and Nicobar Islands, located in the Andaman Sea between peninsular India and Indo-Malaya, are part of two of the 34 mega-diversity hotspots of the world. These islands are characterized by their unique vegetation types such as littoral, mangroves, wet and semi-evergreen forests, and rainforests and for being the home for six aboriginal tribes of Negrito<span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN"> <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">and<span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN"> <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-IN">Mongoloid <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">descent. The islands are also home to a number of migrants and “settlers” from the Indian mainland and Myanmar. The aboriginal tribes and the settlers have a long history of association with the island’s bioresources. In this paper, we survey the ethnic uses of rattans, the unique climbing palms, about 63% of which are endemic to these islands. Our ethnobotanical survey revealed several uses of rattans by the<span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN"> <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-IN">Nicobarese<span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN"> <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">and<span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN"> <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-IN">Shompens, the two major ethnic communities <span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; color: black; mso-ansi-language: EN-IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-IN">of the Nicobar Islands. In this study, besides the ethnic uses, we also estimated the revenue generated among those involved in the rattan trade (collectors, processors, and exporters).